2022
DOI: 10.20873/jbb.uft.cemaf.v10n3.neves
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological and developmental parameters of maize varieties

Abstract: Knowing the characteristics of maize varieties becomes a strategy for an adequate crop planning, in order to extract the maximum agronomic power of each variety. The objective of this work is to know the morphophysiological and developmental parameters of maize varieties. The experiment was conducted in August 2021, in Faculdades Integradas Stella Maris (FISMA), located in the Municipality of Andradina, State of São Paulo. The design was entirely randomized, where six maize varieties were grown: XB 8010; AG 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This compound can also affect stomata, as shown in a study conducted by Mulyono et al (2022) on induced hybrid maize lines (Zea mays L.), where it caused lower stomatal density but larger stomatal size. Similar results were also obtained in a study by de Oliveira Neves et al (2022) on olive trees (Olea europaea L.). Detecting plant mutations using the phenotypic method has been reported to face several limitations (Garcia et al 2016).…”
Section: Introductionsupporting
confidence: 89%
“…This compound can also affect stomata, as shown in a study conducted by Mulyono et al (2022) on induced hybrid maize lines (Zea mays L.), where it caused lower stomatal density but larger stomatal size. Similar results were also obtained in a study by de Oliveira Neves et al (2022) on olive trees (Olea europaea L.). Detecting plant mutations using the phenotypic method has been reported to face several limitations (Garcia et al 2016).…”
Section: Introductionsupporting
confidence: 89%
“…The residue left by the herbicide in the soil implies a toxicity in the plant, in this way, the action of high concentrations results in injuries and leaf necrosis, this phenomenon reflects negatively on the development of the plant, due to the impairment in the multiplication of its cells and also in their differentiation in the stomatal complex, starting to reflect in the number of stomata and this negative response in their functionality was also expected . Studies show that the high correlation between stomatal density and plant dry mass, as reported by Neves et al, (2022), may have compromised CO2 fixation in peanut dry mass.…”
Section: Resultsmentioning
confidence: 94%
“…Plants may change stomatal density when they are under nutritional restriction (Mirjalili et al, 2022;Wang et al, 2018), with water restriction (Hao et al, 2019); salt stress (Pompelli et al, 2021) and even species and varieties (Neves et al, 2022). in greater productivity.…”
Section: )mentioning
confidence: 99%